Study on safety health of construction workers at workplace: a sustainable perspective approach - Kumar Singh, Atul; Aljohani, Abdulelah; Shakor, Pshtiwan; Awuzie, Bankole Osita; Uddin, S. M. Jamil; Shivendra, B. T. (Frontiers in Built Environment, 2024)
In the construction industry, irregular schedules and long hours disrupt workers’ circadian rhythms, adversely affecting their safety and health. While studies have shown that sleep timing influences safety and health, they often overlook sleep quantity, work-shift start time, and a broad range of safety and health outcomes. To fill this gap, this study examines the relationship between circadian rhythm and safety health factors, including psychological issues, wellbeing, behavioral issues, altruistic behaviors, sleep quantity, starting hours at work, and parental care in 1,400 construction workers using a questionnaire. We investigated safety health using scales for psychological issues (0–34), wellbeing (0–24), behavioral issues (0–29), and altruistic behaviors (0–27). Midsleep time on weekends estimated circadian rhythm, with multilevel regressions adjusting for sleep quantity, work start time, and various characteristics. Results showed average midsleep at 04:11 h, with a 1 h delay associated with increased psychological issues (0.37), behavioral issues (3.0%), decreased wellbeing (0.19), and decreased altruistic behaviors (0.18). These findings highlight a correlation between early circadian rhythm and poor safety health, independent of sleep quantity and work-shift start time. Addressing circadian rhythm disruptions could be crucial for improving safety health outcomes, suggesting that work schedule adjustments and better sleep practices may mitigate adverse effects on workers’ health and wellbeing.